Du statique au dynamique : projets photographiques pour le Web - Parent, Sylvie (Ciel variable, 2007)
In this essay, the author looks into photographic practices of recent years that use the fluid space of the World Wide Web as their production and exhibition medium, forgoing the static quality of printed images. The text presents a selection of works from various stages in the Web's evolution and highlights the tension between the static condition of photographs and the dynamic nature of the Internet. Within the context of the World Wide Web, still images embody a certain resistance to mobility but also offer new artistic possibilities due to the Web's characteristics.